2009
DOI: 10.1029/2009ja014277
|View full text |Cite
|
Sign up to set email alerts
|

Response of convection electric fields in the magnetosphere to IMF orientation change

Abstract: [1] The transient response of convection electric fields in the inner magnetosphere to southward turning of the interplanetary magnetic field (IMF) is investigated using in-situ electric field observations by the CRRES and Akebono spacecraft. Electric fields earthward of the inner edge of the electron plasma sheet show quick responses simultaneously with change in ionospheric electric fields, which indicates the arrival of the first signal related to southward turning. A coordinated observation of the electric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…[33] Early observations of near-Earth convection by Aggson and Heppner [1977] showed the presence of large electric field in the inner magnetosphere during the substorm growth phase. Recently Nishimura et al [2009] also found that convective electric field enhancement in the inner magnetosphere has a very small time delay (∼5 min) relative to IMF southward turning, whereas electric field enhance-ment in the outer magnetosphere has a more pronounced delay (∼30 min). Our work is consistent with this picture: delayed response in the outer magnetosphere is caused by storage of magnetic flux in the tail and suppression of earthward convection, whereas the onset of the flux transport is likely related to the release of magnetic flux due to tail reconnection.…”
Section: Discussionmentioning
confidence: 93%
“…[33] Early observations of near-Earth convection by Aggson and Heppner [1977] showed the presence of large electric field in the inner magnetosphere during the substorm growth phase. Recently Nishimura et al [2009] also found that convective electric field enhancement in the inner magnetosphere has a very small time delay (∼5 min) relative to IMF southward turning, whereas electric field enhance-ment in the outer magnetosphere has a more pronounced delay (∼30 min). Our work is consistent with this picture: delayed response in the outer magnetosphere is caused by storage of magnetic flux in the tail and suppression of earthward convection, whereas the onset of the flux transport is likely related to the release of magnetic flux due to tail reconnection.…”
Section: Discussionmentioning
confidence: 93%
“…However, for strong magnetic field at low altitudes, diffusion is very slow and results in very weak fluxes of energetic electrons for forbidden drift shells. In contrast, geomagnetic storms, large substorms, and sudden commencements or magnetospheric compressions are accompanied by a very strong penetrating EF in the dawn-dusk direction of approximately a few mV/m [e.g., Nishimura et al, 2006Nishimura et al, , 2009Shinbori et al, 2006;Fejer et al, 2007;Lazutin and Kuznetsov, 2008]. On the nightside, this EF is pointed westward and results in the fast (a few hours) ExB drift of particles across magnetic field lines toward the Earth.…”
Section: Discussionmentioning
confidence: 99%
“…The EIW model predicts that the electric field associated with the ionospheric currents is transmitted into the magnetosphere by the Alfven waves along the magnetic field lines. Thus, the PI electric field is detected by the HF Doppler observations in the low‐latitude F region ionosphere [ Kikuchi , ] and by satellites in the inner magnetosphere [ Nishimura et al ., ]. Furthermore, upward flow of the Poynting flux was observed in the inner magnetosphere as predicted by the EIW model [ Nishimura et al ., ].…”
Section: Introductionmentioning
confidence: 97%